Integration of reverse engineering and non-linear numerical analysis for the seismic assessment of historical adobe buildings - Aguilar R. (2019)
This research was performed by the Engineering & Heritage research group at PUCP with collaboration from the Department of Structural Engineering of the University of Minho in Portugal. The authors would like to acknowledge the Directorate of Research Management at PUCP (project N° 349-2016) for funding this research. The second author also gratefully acknowledges CONCYTEC for the scholarship in support of her Master studies (Contract N° 027-2015 FONDECYT). Finally, the authors acknowledge the special support provided by the order of the Jesuits and the research assistant Rossemary Enciso.